Kinematic measurement of wheelchair racing using smartphones : a case study - Chow, Kin Ming (2017)
Wheelchair sprint events are one of the most popular events amongst para-sports. With an increase in the popularity of para-sports, there is a need to provide quantitative analysis for high-performance wheelchair sprinters. Current protocols are limited by the inability to assess biomechanical data during race events. This study puts forth the possibility of using the smartphone, a lightweight and easily-accessible device, coupled with commercially-available data recording software, as an alternative to other kinematic recording devices. This setup allows us to collect acceleration data and derive the biomechanical outputs, employing a model reported in the literature. This study compares the validity of an Android accelerometer application, installed on a Samsung Galaxy A3 (2016), against an InertialLabs OS3D Miniature Orientation Sensor. The kinematics of the wheelchair athlete will be determined by an analytical model, taking into account the athlete’s anthropometrics, acceleration data from both accelerometers, and the measurements of the racing wheelchair. A Paralympic wheelchair racing athlete was instrumented with a smartphone recording device, and a commercial accelerometer, and accelerometer data will be recorded for 60m and 120m maximal trials. It was found that the smartphone was not in good agreement with the benchmark IMU for determining wheelchair racing kinematics.